Application of Information Technologies of Interactive Methods in Teaching Foreign Languages in Non-Philological Universities - Sheralieva Shakhnoza Irkinovna (Genius Journals, 2022)
The article provides specific examples from the practice of the author's work in the study of a foreign language in a technical university. The effectiveness of the use of various methods in the process of learning a foreign language in a non-philological university is substantiated.
Keywords: foreign language; technical university; student; teacher